Koto Gadang in Local History: A Nagari That Forming 20th Century Indonesian Intellectuals - Budi Darmawan; Endah Regita Cahyani Nazra (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Koto Gadang is a traditional village in Minangkabau, which gave birth to and formed many Indonesian intellectuals or political figures in the period before the early days of Indonesian independence in various schools of thought, which in this article is a study of local history. This study analyzes the role of the Koto Gadang nagari from the perspective of local history studies which were the factors that shaped the birth and contribution of Indonesian intellectuals in the 20th century. The method used in this article is the historical method, namely heuristics, source verification, interpretation and historiography. This research shows that Koto Gadang was a very important nagari for the Indonesian people in the 20th century. Nagari Koto Gadang is a small village whose people live from craftsmen and agriculture. Situated in a highland area flanked by Mount Marapi and Mount Singgalang, this does not make Koto Gadang a village left behind in the 20th century. Even though there is little agricultural land and an emphasis on craftsmen, the Koto Gadang village has succeeded in providing its children with a good education. Thanks to progress in the field of education and the open attitude of society, this village has become one of the contributors to Indonesian intellectuals. Koto Gadang adalah sebuah desa tradisional di Minangkabau, yang melahirkan dan membentuk banyak cendekiawan atau tokoh perpolitikan Indonesia pada masa sebelum masa awal-awal kemerdekan Indonesia dalam berbagai aliran pemikiran, yang dalam artikel ini sebagai kajian sejarah lokal. Kajian ini menganalisis tentang peran nagari Koto Gadang dari sudut kajian sejarah lokal yang menjadi faktor pembentuk lahirnya dan penyumbang cendekiawan Indonesia pada abad ke 20. Metode yang digunakan dalam artikel ini ialah metode sejarah yaitu heuristik, kritik sumber, interpretasi, dan historiografi. Penelitian ini menunjukkan bahwa Koto Gadang adalah sebuah nagari yang sangat penting bagi bangsa Indonesia pada abad ke 20-an. Nagari Koto Gadang merupakan nagari kecil yang masyarakatnya hidup dari bidang pengrajin dan pertanian. Terletak di daerah dataran tinggi yang diapit oleh Gunung Marapi dan Gunung Singgalang ini tidak membuat Koto Gadang menjadi nagari yang tertinggal pada abad ke-20. Meskipun lahan pertanian sedikit dan menitikberatkan pengrajin, nagari Koto Gadang berhasil mengiringi anak-anaknya dengan pendidikan yang maju. Berkat kemajuan bidang Pendidikan dan sikap keterbukaan masyarakat membuat nagari ini menjadi salah satu penyumbang cendekiawan Indonesia.